Adenoid cystic carcinoma of the breast: multimodality imaging findings and review of the literature - BUĞDAYCI, ONUR (My University, 2022)
© 2022 The Association of University RadiologistsRationale and Objectives: Adenoid cystic carcinoma (ACC) of the breast is a rare type of breast cancer with favorable prognosis. There is limited data on the radiological findings of this rare tumor in literature. The aim of this study is to determine the most common imaging features and review the literature. Materials and Methods: Pathological databases of seven institutions from 2009 to 2021 were retrospectively reviewed, and patients with a diagnosis of ACC of the breast were determined. Thirteen patients whose imaging studies could be recalled from the picture archiving systems (PACS) were included in the study. Clinical and pathological findings as well as follow-up data were recorded. Radiological findings were analyzed and categorized based on BI-RADS 5th edition. Results: There were 16 mass lesions in 13 patients (two multifocal cases, one case with recurrence). Mammography demonstrated 14 masses, while ultrasound (US) demonstrated all. MRI was available in only seven cases, with eight masses. The most common findings were round or oval shape on all modalities (78.57%–93.75%). Other frequent findings were parallel orientation (81.25%), isoechoic or hyperechoic echogenicity (62.5%), high T2 signal (87.5%), restricted diffusion (71.43%), and homogeneous enhancement (62.5%). Mammography, US and MRI showed circumscribed margins resembling a benign lesion in 35.71%, 37.5% and 50% of the lesions respectively. Three patients had a cyst-like echogenicty on US. Half of the lesions were avascular on Doppler US (6/12) and half were soft (2/4) on strain elastography. Although there were benign features on all imaging modalities seperately, all lesions could be categorized as BI-RADS 4 or 5 when the findings were combined. However 9/16 masses were BI-RADS 4A, emphasizing the subtlety of the malignant features. Conclusion: ACC of the breast can present with findings resembling a benign lesion on different imaging modalities. Although combination of all imaging findings correctly indicated the suspicious nature of the lesions in all cases, final classification was BI-RADS 4A in most of them. Radiologists should be aware of the more frequent findings of ACC of the breast for early diagnosis. US findings of isoechoic or hyperechoic appearance, and cyst-like echogenicity have not been reported previously in literature.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Clinical Medicine (MED); CLINICAL MEDICINE; RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging; Adenoid cystic carcinoma; breast; mammography; MRI; ultrasound